Ferrite material with high saturation magnetic flux density, high frequency and low loss and preparation method thereof
By optimizing the composition and preparation process of manganese-zeb ferrite materials, the problem that the material is difficult to have high saturation flux density and low loss at high frequencies is solved, and the magnetic properties with low loss at high frequencies are achieved to meet the needs of high-frequency transformers.
Patent Information
- Application Number
- CN202411972483.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-08
AI Technical Summary
Manganese-zeb ferrite materials are difficult to have high saturation flux density and low loss at high frequencies, and cannot meet the low loss requirements of high-frequency transformers.
By optimizing the ratio of main components and sub-components, including main components such as Fe2O3, ZnO, NiO, MnO, and sub-components such as Co2O3, SiO2, CaCO3, Nb2O5, ZrO2, V2O5, and specific preparation processes are adopted, such as pre-sintering, crushing, granulation, molding and sintering, the sintering temperature and oxygen concentration are controlled, and the microstructure and magnetic properties of the material are optimized.
The saturation flux density of ferrite materials at 100°C is achieved by achieving a lower core loss than 490mT at 100°C, and the core loss is lower than the expected value at 1-3MHz, meeting the low loss requirements of high-frequency transformers.
Smart Images

Figure BDA0005219764220000111
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of manganese-zinc ferrite materials, and in particular relates to a high-saturation magnetic flux density, high-frequency and low-loss ferrite material and a preparation method thereof. Background Art
[0002] With the development of artificial intelligence, big data centers are booming. It is predicted that the electricity consumed by global data centers will reach 3000TWh in 2030, growing at an average annual rate of more than 20%. Processors such as CPUs and GPUs in data centers are the core power consumption points. The general chip power supply method is that the AC 110-220V mains electricity is transformed into 12V-24V DC after AC-DC and DC-DC, and then stepped down by the Buck circuit to form a voltage of 0.5-3V to power the chip. With the advancement of semiconductor chip manufacturing technology, the operating voltage of the chip is getting lower and lower, but the power of the chip is constantly increasing, resulting in an increasing current directly supplying power to the chip. At the same time, in order to reduce the volume of capacitors and inductors in the circuit, the switching frequency of the Buck circuit is getting higher and higher.
[0003] Buck circuit is a DC-DC converter based on inductor and capacitor energy storage. By controlling the PWM wave to switch the switch state, the input voltage is converted into an adjustable low-voltage output to meet the power supply requirements of different circuits. In the Buck step-down circuit, the power inductor is the core energy storage component. And soft magnetic materials are the core materials in power inductors. Its saturation flux density and high-frequency loss characteristics directly affect the working state of the power inductor. The saturation flux density of the material determines the size of the DC superposition current, while the loss affects the power conversion efficiency of the entire circuit. Therefore, it is hoped that the soft magnetic material in the inductor has the characteristics of high saturation flux density and high frequency and low loss.
[0004] Manganese-zinc ferrite materials and metal powder core materials are two important magnetic materials currently used in power inductors. Compared with metal powder core materials, manganese-zinc ferrite materials have lower losses at high frequencies of 1-2MHz. Therefore, in terms of conversion efficiency, manganese-zinc ferrite materials have advantages over metal powder core materials. However, the saturation flux density of manganese-zinc ferrite materials is lower than that of metal powder core materials, only about half of that of metal powder core materials. As the working current increases, ferrite materials need to increase their saturation flux density to meet the needs of chip circuit technology development.
[0005] Through the investigation of the published literature such as CN115340372A, CN109133899A, CN109354489A, CN112661502A, CN105645945A, CN111039666A, CN114133233A, CN114085077A, CN107352991A, CN116813320A, CN118299136A, it is found that the common method to reduce the high-frequency loss of manganese-zinc ferrite is to obtain a microstructure with fine grains and a core-shell structure by optimizing the composition and the preparation process, reduce the hysteresis coefficient by ion replacement, or reduce the loss at high frequency by adding low-melting-point substances and reducing the sintering temperature. However, the saturation flux density of the material at 100°C did not exceed 460mT.
[0006] The patent with publication number CN118812255A discloses a high-frequency, high-Bs, high-DC superposition, low-loss ferrite material obtained by NiO substitution. The NiO substitution amount is 1.8-4.5 mol%. The material has low loss at 1-3 MHz, but the saturation flux density at 100°C is around 460 mT. Summary of the invention
[0007] The object of the present invention is to provide a high saturation magnetic flux density, high frequency and low loss ferrite material and a preparation method thereof, so as to solve the problem that manganese-zinc ferrite cannot have both high saturation magnetic flux density and low loss at high frequency.
[0008] The purpose of the present invention can be achieved by the following technical solutions:
[0009] A high saturation flux density, high frequency and low loss ferrite material, characterized in that it is composed of a main component and a subsidiary component, the main component includes Fe2O3, ZnO, NiO and MnO remainder; the subsidiary components include Co2O3, SiO2, CaCO3, Nb2O5, ZrO2 and V2O5.
[0010] Furthermore, the main components are composed of Fe2O3: 56.83-57.41mol%, ZnO: 3.5-4.5mol%, NiO: 4.5-5.5mol% and MnO as the balance; the sub-components include Co2O3: 0.22-0.30wt%, SiO2: 0.005-0.012wt%, CaCO3: 0.06-0.12wt%, Nb2O5: 0.01-0.04wt%, ZrO2: 0.01-0.03wt% and V2O5: 0.01-0.03wt%, measured by the weight of the main components.
[0011] A method for preparing a high saturation magnetic flux density, high frequency and low loss ferrite material, characterized in that it comprises the following steps: batching, pre-sintering, crushing, granulating, molding and sintering.
[0012] Furthermore, the specific steps of the batching are:
[0013] Fe2O3, MnO, NiO and ZnO are weighed according to the proportion and mixed and sand-milled for 20-30 minutes to obtain a mixed powder.
[0014] Furthermore, the specific steps of the pre-burning are:
[0015] The mixed powder is dried and then pre-fired in a muffle furnace at a pre-fired temperature of 850-950° C. for 3-5 hours to obtain a pre-fired material.
[0016] Furthermore, the specific steps of the crushing are:
[0017] The auxiliary components are added to the pre-sintered material and crushed for 60-90 minutes. The particle size after crushing is 0.8-1.0 μm to obtain crushed slurry.
[0018] Furthermore, the specific steps of the granulation are:
[0019] After the crushed slurry is dried, 0.8-1.0 wt% of PVA is added to the crushed slurry for granulation to obtain particles.
[0020] Furthermore, the specific steps of the forming are:
[0021] The granulated particles are pressed and the green compact density is controlled at 3.0±0.1g / cm 3 , and obtain the blank.
[0022] Furthermore, the specific steps of sintering are:
[0023] The blank is sintered in a kiln at a sintering temperature of 1050-1150°C for 3-5h and an oxygen concentration of 1.0-2.5%. After the insulation is completed, the sintering temperature is lowered to room temperature at a rate of 50-200°C / h to obtain a ferrite material.
[0024] Furthermore, the oxygen concentration PO2 during the cooling process from the sintering temperature to 950°C is controlled according to lgPO2=a / T+b for balanced oxygen concentration, where a is between -10000 and -15000, b is between 5 and 8, and T is the absolute temperature K.
[0025] Beneficial effects of the present invention:
[0026] (1) The ferrite material prepared by the present invention has both a higher saturation magnetic flux density and a lower core loss at high frequencies.
[0027] (2) The present invention controls the introduction of the fourth main component NiO, the composition of the auxiliary components and the optimization of the preparation process, so that the saturation flux density of the ferrite material prepared at 100°C is greater than 490mT; at the same time, the core loss at 1MHz, 50mT is less than 120kW / m at 25°C and 100°C, respectively. 3 and 130kW / m 3 , at 2MHz, the loss at 50mT is less than 400kW / m at 25℃ and 100℃ respectively 3 and 450kW / m 3 , at 3MHz, 50mT, the loss is less than 1200kW / m at 25℃ and 100℃ respectively 3 and 1300kW / m 3 , so that the manganese-zinc ferrite material can adapt to the low loss requirements of high-frequency transformers in switching power supplies at high frequencies. DETAILED DESCRIPTION
[0028] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0029] Example 1
[0030] This embodiment provides a high saturation magnetic flux density, high frequency and low loss ferrite material, which is prepared by the following steps:
[0031] (1) Ingredients: Fe2O3: 56.83 mol%, ZnO: 4.0 mol%, NiO: 5.5 mol%, and the balance MnO are weighed and mixed and sand-milled for 20 min to obtain a mixed powder;
[0032] (2) Pre-burning: After drying the mixed powder, pre-burn it in a muffle furnace at a pre-burning temperature of 900° C. for 3 h to obtain a pre-burned material;
[0033] (3) Crushing: adding 0.30wt% of Co2O3, 0.01wt% of SiO2, 0.06wt% of CaCO3, 0.01wt% of Nb2O5, 0.01wt% of ZrO2, and 0.03wt% of V2O5, based on the weight of the main components, to the pre-calcined material for crushing. The crushing time is 90 min. The particle size after crushing is 0.82 μm, and a crushed slurry is obtained.
[0034] (4) Granulation: After drying the crushed slurry, 1.0 wt% of PVA was added to the crushed slurry for granulation to obtain granules;
[0035] (5) Molding: The granulated particles are pressed and the green compact density is controlled at 3.0 g / cm 3 , and obtain the blank.
[0036] (6) Sintering: The blank is sintered in a kiln at a sintering temperature of 1150°C for 3 hours; the oxygen concentration during the insulation is 1.0%. After the insulation is completed, the sintering temperature is cooled to room temperature at a rate of 100°C / h to obtain a ferrite material; during the process of cooling from the sintering temperature to 950°C, the oxygen concentration PO2 is controlled according to lgPO2=a / T+b to balance the oxygen concentration, where a is -14500, b is 8, and T is the absolute temperature K.
[0037] Example 2
[0038] This embodiment provides a high saturation magnetic flux density, high frequency and low loss ferrite material, which is prepared by the following steps:
[0039] (1) Ingredients: Fe2O3: 57.12 mol%, ZnO: 4.0 mol%, NiO: 5.0 mol%, and the balance MnO are weighed and mixed and sand-milled for 30 min to obtain a mixed powder;
[0040] (2) Pre-burning: After drying the mixed powder, pre-burn it in a muffle furnace at a pre-burning temperature of 950° C. for 3 h to obtain a pre-burned material;
[0041] (3) Crushing: adding 0.30 wt% of Co2O3, 0.008 wt% of SiO2, 0.06 wt% of CaCO3, 0.025 wt% of Nb2O5, 0.02 wt% of ZrO2, and 0.03 wt% of V2O5, based on the weight of the main components, to the pre-calcined material for crushing. The crushing time is 90 min. The particle size after crushing is 0.96 μm, and a crushed slurry is obtained.
[0042] (4) Granulation: After drying the crushed slurry, 0.8 wt% of PVA by weight of the crushed slurry is added to granulate to obtain granules;
[0043] (5) Molding: The granulated particles are pressed and the green compact density is controlled at 3.05 g / cm 3 , and obtain the blank.
[0044] (6) Sintering: The blank is sintered in a kiln at a sintering temperature of 1100°C for 3 hours; the oxygen concentration during the insulation is 1.5%. After the insulation is completed, the sintering temperature is cooled to room temperature at a rate of 100°C / h to obtain a ferrite material; the oxygen concentration PO2 during the cooling process from the sintering temperature to 950°C is controlled according to lgPO2=a / T+b to balance the oxygen concentration, where a is -12100, b is 5, and T is the absolute temperature K.
[0045] Example 3
[0046] This embodiment provides a high saturation magnetic flux density, high frequency and low loss ferrite material, which is prepared by the following steps:
[0047] (1) Ingredients: Fe2O3: 57.35 mol%, ZnO: 4.15 mol%, NiO: 4.75 mol%, and the balance MnO are weighed and mixed and sand-milled for 20 min to obtain a mixed powder;
[0048] (2) Pre-burning: After drying the mixed powder, pre-burn it in a muffle furnace at a pre-burning temperature of 850° C. for 3 h to obtain a pre-burned material;
[0049] (3) Crushing: adding 0.25wt% of Co2O3, 0.012wt% of SiO2, 0.07wt% of CaCO3, 0.04wt% of Nb2O5, 0.02wt% of ZrO2, and 0.01wt% of V2O5, based on the weight of the main components, to the pre-calcined material for crushing. The crushing time is 75 min. The particle size after crushing is 0.85 μm, and a crushed slurry is obtained.
[0050] (4) Granulation: After drying the crushed slurry, 0.8 wt% of PVA by weight of the crushed slurry is added to granulate to obtain granules;
[0051] (5) Molding: The granulated particles are pressed and the green compact density is controlled at 3.0 g / cm 3 , and obtain the blank.
[0052] (6) Sintering: The blank is sintered in a kiln at a sintering temperature of 1050°C for 5 hours; the oxygen concentration during the insulation is 1.0%. After the insulation is completed, the sintering temperature is cooled to room temperature at a rate of 100°C / h to obtain a ferrite material; the oxygen concentration PO2 during the cooling process from the sintering temperature to 950°C is controlled according to lgPO2=a / T+b to balance the oxygen concentration, where a is -14500, b is 8, and T is the absolute temperature K.
[0053] Example 4
[0054] This embodiment provides a high saturation magnetic flux density, high frequency and low loss ferrite material, which is prepared by the following steps:
[0055] (1) Ingredients: Fe2O3: 57.41 mol%, ZnO: 4.50 mol%, NiO: 4.50 mol%, and the balance MnO are weighed and mixed and sand-milled for 30 min to obtain a mixed powder;
[0056] (2) Pre-burning: After drying the mixed powder, pre-burn it in a muffle furnace at a pre-burning temperature of 950° C. for 3 h to obtain a pre-burned material;
[0057] (3) Crushing: adding 0.22 wt % of Co2O3, 0.008 wt % of SiO2, 0.09 wt % of CaCO3, 0.02 wt % of Nb2O5, 0.01 wt % of ZrO2 and 0.01 wt % of V2O5, based on the weight of the main components, to the pre-calcined material for crushing. The crushing time is 90 min. The particle size after crushing is 0.96 μm, and a crushed slurry is obtained.
[0058] (4) Granulation: After drying the crushed slurry, 0.8 wt% of PVA by weight of the crushed slurry is added to granulate to obtain granules;
[0059] (5) Molding: The granulated particles are pressed and the green compact density is controlled at 3.0 g / cm 3 , and obtain the blank.
[0060] (6) Sintering: The blank is sintered in a kiln at a sintering temperature of 1150°C for 5 hours; the oxygen concentration during the insulation is 1.0%. After the insulation is completed, the sintering temperature is cooled to room temperature at a rate of 100°C / h to obtain a ferrite material; the oxygen concentration PO2 during the cooling process from the sintering temperature to 950°C is controlled according to lgPO2=a / T+b to balance the oxygen concentration, where a is -10500, b is 5.5, and T is the absolute temperature K.
[0061] Example 5
[0062] This embodiment provides a high saturation magnetic flux density, high frequency and low loss ferrite material, which is prepared by the following steps:
[0063] (1) Ingredients: Fe2O3: 57.12 mol%, ZnO: 3.75 mol%, NiO: 5.25 mol%, and the balance MnO are weighed and mixed and sand-milled for 30 min to obtain a mixed powder;
[0064] (2) Pre-burning: After drying the mixed powder, pre-burn it in a muffle furnace at a pre-burning temperature of 950° C. for 3 h to obtain a pre-burned material;
[0065] (3) Crushing: adding 0.28 wt % of Co2O3, 0.009 wt % of SiO2, 0.11 wt % of CaCO3, 0.02 wt % of Nb2O5, 0.02 wt % of ZrO2, and 0.03 wt % of V2O5, based on the weight of the main components, to the pre-calcined material for crushing. The crushing time is 90 min. The particle size after crushing is 0.96 μm, and a crushed slurry is obtained.
[0066] (4) Granulation: After drying the crushed slurry, 0.8 wt% of PVA by weight of the crushed slurry is added to granulate to obtain granules;
[0067] (5) Molding: The granulated particles are pressed and the green compact density is controlled at 3.0 g / cm 3 , and obtain the blank.
[0068] (6) Sintering: The blank is sintered in a kiln at a sintering temperature of 1150°C for 5 hours; the oxygen concentration during the insulation is 1.0%. After the insulation is completed, the sintering temperature is cooled to room temperature at a rate of 100°C / h to obtain a ferrite material; the oxygen concentration PO2 during the cooling process from the sintering temperature to 950°C is controlled according to lgPO2=a / T+b to balance the oxygen concentration, where a is -13500, b is 5.5, and T is the absolute temperature K.
[0069] Example 6
[0070] This embodiment provides a high saturation magnetic flux density, high frequency and low loss ferrite material, which is prepared by the following steps:
[0071] (1) Ingredients: Fe2O3: 57.35 mol%, ZnO: 3.50 mol%, NiO: 5.50 mol%, and the balance MnO are weighed and mixed and sand-milled for 30 min to obtain a mixed powder;
[0072] (2) Pre-burning: After drying the mixed powder, pre-burn it in a muffle furnace at a pre-burning temperature of 950° C. for 3 h to obtain a pre-burned material;
[0073] (3) Crushing: adding 0.30 wt% of Co2O3, 0.01 wt% of SiO2, 0.12 wt% of CaCO3, 0.02 wt% of Nb2O5, 0.03 wt% of ZrO2 and 0.03 wt% of V2O5, based on the weight of the main components, to the pre-calcined material for crushing. The crushing time is 90 min. The particle size after crushing is 0.96 μm to obtain a crushed slurry.
[0074] (4) Granulation: After drying the crushed slurry, 0.8 wt% of PVA by weight of the crushed slurry is added to granulate to obtain granules;
[0075] (5) Molding: The granulated particles are pressed and the green compact density is controlled at 3.0 g / cm 3 , and obtain the blank.
[0076] (6) Sintering: The blank is sintered in a kiln at a sintering temperature of 1150°C for 5 hours; the oxygen concentration during the insulation is 1.0%. After the insulation is completed, the sintering temperature is cooled to room temperature at a rate of 100°C / h to obtain a ferrite material; the oxygen concentration PO2 during the cooling process from the sintering temperature to 950°C is controlled according to lgPO2=a / T+b to balance the oxygen concentration, where a is -13500, b is 5.5, and T is the absolute temperature K.
[0077] Comparative Example 1
[0078] This comparative example provides a ferrite material, which is prepared by the following steps:
[0079] (1) Ingredients: Fe2O3: 54.20 mol%, ZnO: 4.0 mol%, and the balance MnO are weighed and mixed and sand-milled for 20 min to obtain a mixed powder;
[0080] (2) Pre-burning: After drying the mixed powder, pre-burn it in a muffle furnace at a pre-burning temperature of 900° C. for 3 h to obtain a pre-burned material;
[0081] (3) Crushing: adding 0.30wt% of Co2O3, 0.01wt% of SiO2, 0.06wt% of CaCO3, 0.01wt% of Nb2O5, 0.01wt% of ZrO2, and 0.03wt% of V2O5, based on the weight of the main components, to the pre-calcined material for crushing. The crushing time is 90 min. The particle size after crushing is 0.82 μm, and a crushed slurry is obtained.
[0082] (4) Granulation: After drying the crushed slurry, 1.0 wt% of PVA was added to the crushed slurry for granulation to obtain granules;
[0083] (5) Molding: The granulated particles are pressed and the green compact density is controlled at 3.0 g / cm 3 , and obtain the blank.
[0084] (6) Sintering: The blank is sintered in a kiln at a sintering temperature of 1150°C for 3 hours; the oxygen concentration during the insulation is 1.0%. After the insulation is completed, the sintering temperature is cooled to room temperature at a rate of 100°C / h to obtain a ferrite material; during the process of cooling from the sintering temperature to 950°C, the oxygen concentration PO2 is controlled according to lgPO2=a / T+b to balance the oxygen concentration, where a is -14500, b is 8, and T is the absolute temperature K.
[0085] Comparative Example 2
[0086] This comparative example provides a ferrite material, which is prepared by the following steps:
[0087] (1) Ingredients: Fe2O3: 56.83 mol%, ZnO: 4.5 mol%, NiO: 4.5 mol%, and the balance MnO are weighed and mixed and sand-milled for 30 min to obtain a mixed powder;
[0088] (2) Pre-burning: After drying the mixed powder, pre-burn it in a muffle furnace at a pre-burning temperature of 1050° C. for 3 h to obtain a pre-burned material;
[0089] (3) Crushing: adding 0.30 wt % of Co2O3, 0.015 wt % of SiO2, 0.16 wt % of CaCO3, 0.01 wt % of Nb2O5, 0.04 wt % of ZrO2, and 0.06 wt % of V2O5, based on the weight of the main components, to the pre-calcined material for crushing. The crushing time is 40 min. The particle size after crushing is 1.54 μm, and a crushed slurry is obtained.
[0090] (4) Granulation: After drying the crushed slurry, 1.0 wt% of PVA was added to the crushed slurry for granulation to obtain granules;
[0091] (5) Molding: The granulated particles are pressed and the green compact density is controlled at 3.0 g / cm 3 , and obtain the blank.
[0092] (6) Sintering: The blank is sintered in a kiln at a sintering temperature of 1150°C for 5 hours; the oxygen concentration during the insulation is 1.5%. After the insulation is completed, the sintering temperature is cooled to room temperature at a rate of 100°C / h to obtain a magnetic ring; the oxygen concentration PO2 during the cooling process from the sintering temperature to 950°C is controlled according to lgPO2=a / T+b to balance the oxygen concentration, where a is -15500, b is 2.5, and T is the absolute temperature K;
[0093] 7) Magnetic heat treatment: The sintered magnetic ring is heat treated at 550°C, and a magnetic field of 200A / m is added during the heat treatment to obtain a ferrite material.
[0094] Comparative Example 3
[0095] This comparative example provides a ferrite material, which is prepared by the following steps:
[0096] (1) Ingredients: Fe2O3: 57.41 mol%, ZnO: 4.0 mol%, NiO: 5.5 mol%, and the balance MnO are weighed and mixed and sand-milled for 30 min to obtain a mixed powder;
[0097] (2) Pre-burning: After drying the mixed powder, pre-burn it in a muffle furnace at a pre-burning temperature of 1050° C. for 3 h to obtain a pre-burned material;
[0098] (3) Crushing: adding 0.22 wt % of Co2O3, 0.015 wt % of SiO2, 0.16 wt % of CaCO3, 0.01 wt % of Nb2O5, 0.04 wt % of ZrO2, and 0.06 wt % of V2O5, based on the weight of the main components, to the pre-calcined material for crushing. The crushing time is 40 min. The particle size after crushing is 1.54 μm, and a crushed slurry is obtained.
[0099] (4) Granulation: After drying the crushed slurry, 1.0 wt% of PVA was added to the crushed slurry for granulation to obtain granules;
[0100] (5) Molding: The granulated particles are pressed and the green compact density is controlled at 3.0 g / cm 3 , and obtain the blank.
[0101] (6) Sintering: The blank is sintered in a kiln at a sintering temperature of 1150°C for 5 hours; the oxygen concentration during the insulation is 1.5%. After the insulation is completed, the sintering temperature is cooled to room temperature at a rate of 100°C / h to obtain a ferrite material; during the process of cooling from the sintering temperature to 950°C, the oxygen concentration PO2 is controlled according to lgPO2=a / T+b to balance the oxygen concentration, where a is -15500, b is 2.5, and T is the absolute temperature K.
[0102] The ferrite materials prepared in Examples 1 to 6 and Comparative Examples 1 to 3 were subjected to performance tests, and the saturation magnetic flux density Bs, initial magnetic permeability μi at high temperature 100°C and core loss Pcv at high frequency 1-3MHz and 50mT were tested. The results are shown in Table 1:
[0103] Table 1
[0104]
[0105] It can be seen from Table 1 that the ferrite materials prepared in Examples 1 to 6 have higher saturation magnetic flux density and lower core loss at high frequencies.
[0106] Comparison between Comparative Example 1 and Example 1 shows that the saturation flux density of the ferrite material can be effectively improved by introducing NiO into the main component and optimizing the auxiliary components and the preparation process, and a ferrite material with lower loss at 1-3 MHz can be obtained.
[0107] As shown in Comparative Examples 2 and 3, the formula range and preparation process conditions proposed in the present invention are the basic conditions for simultaneously improving the saturation flux density of the ferrite material and having a lower core loss at 1-3 MHz. If the formula range and process conditions are exceeded, the saturation flux density of the ferrite material cannot be improved and the core loss cannot be lowered at 1-3 MHz.
[0108] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.
[0109] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A high saturation flux density, high frequency and low loss ferrite material, characterized in that: It is composed of main components and auxiliary components. The main components include Fe2O3, ZnO, NiO and MnO remainder; the auxiliary components include Co2O3, SiO2, CaCO3, Nb2O5, ZrO2 and V2O5.
2. The high saturation flux density, high frequency and low loss ferrite material according to claim 1, characterized in that: The main components are Fe2O3: 56.83-57.41mol%, ZnO: 3.5-4.5mol%, NiO: 4.5-5.5mol% and MnO as the remainder; the secondary components include Co2O3: 0.22-0.30wt%, SiO2: 0.005-0.012wt%, CaCO3: 0.06-0.12wt%, Nb2O5: 0.01-0.04wt%, ZrO2: 0.01-0.03wt% and V2O5: 0.01-0.03wt%, calculated by the weight of the main components.
3. A method for preparing a high saturation magnetic flux density, high frequency and low loss ferrite material according to any one of claims 1 to 2, characterized in that: The method comprises the following steps: batching, pre-firing, crushing, granulating, molding and sintering.
4. The method for preparing a high saturation magnetic flux density, high frequency and low loss ferrite material according to claim 3, characterized in that: The specific steps of the batching are: Fe2O3, MnO, NiO and ZnO are weighed according to the proportion and mixed and sand-milled for 20-30 minutes to obtain a mixed powder.
5. The method for preparing a high saturation magnetic flux density, high frequency and low loss ferrite material according to claim 3, characterized in that: The specific steps of the pre-burning are: The mixed powder is dried and then pre-fired in a muffle furnace at a pre-fired temperature of 850-950° C. for 3-5 hours to obtain a pre-fired material.
6. The method for preparing a high saturation magnetic flux density, high frequency and low loss ferrite material according to claim 3, characterized in that: The specific steps of the crushing are: The auxiliary components are added to the pre-sintered material and crushed for 60-90 minutes. The particle size after crushing is 0.8-1.0 μm to obtain crushed slurry.
7. The method for preparing a high saturation magnetic flux density, high frequency and low loss ferrite material according to claim 3, characterized in that: The specific steps of the granulation are: After the crushed slurry is dried, 0.8-1.0 wt% of PVA is added to the crushed slurry for granulation to obtain particles.
8. The method for preparing a high saturation magnetic flux density, high frequency and low loss ferrite material according to claim 3, characterized in that: The specific steps of the molding are: The granulated particles are pressed and the green compact density is controlled at 3.0±0.1g / cm 3 , and obtain the blank.
9. The method for preparing a high saturation magnetic flux density, high frequency and low loss ferrite material according to claim 3, characterized in that: The specific steps of sintering are: The blank is sintered in a kiln at a sintering temperature of 1050-1150°C for 3-5h and an oxygen concentration of 1.0-2.5%. After the insulation is completed, the sintering temperature is lowered to room temperature at a rate of 50-200°C / h to obtain a ferrite material.
10. The method for preparing a high saturation magnetic flux density, high frequency and low loss ferrite material according to claim 9, characterized in that: The oxygen concentration PO2 during the cooling process from the sintering temperature to 950°C is controlled by lgPO2=a / T+b for equilibrium oxygen concentration, where a is between -10000 and -15000, b is between 5 and 8, and T is the absolute temperature K.
Citation Information
Patent Citations
High-frequency manganese-zinc ferrite material
CN105645945A
Core-shell structured manganese-zinc / nickel-zinc composite ferrite and preparation method thereof
CN107352991A
High-frequency low-power-consumption magnesium doped manganese zinc ferrite and preparation method thereof
CN109133899A
High-frequency low-loss ferrite material and preparation method thereof
CN109354489A
Ultrahigh saturation flux density manganese-zinc ferrite material and preparation method thereof
CN111039666A